Hubungan Tingkat Pengetahuan dan Sikap Santri Terhadap Kesiapsiagaan dalam Penganggulangan Bencana Kebakaran di Pondok Pesantren X di Kota Surabaya - Friska Ayu; Ratna Ayu Ratriwardhani (UNUSA Press, 2021)
Preparedness is a part of the disaster management process which aims to prevent and minimize disaster risk which is pro-active before a disaster occurs. Fire disasters can occur anywhere, including in the Islamic boarding schools, this is because in the Islamic boarding schools there is not only a teaching and learning process, but there are additional activities such as fulfilling their daily needs such as the students also live in the cottage during their studies. This research was conducted in July-August 2020 which aims to analyze the relationship between the level of knowledge and attitudes of students towards fire disaster preparedness at Islamic Boarding School Pondok Karya at Manado City. Type of this research using analytic survey with a cross sectional approach, with a total sample of 89 people was taken using accidental techniques. The results of this study showed that as many as 60 students (67.4%) have a level of preparedness that is ready to cope with fire disasters with a good level of knowledge (47.2%) on fire management procedures although only 33 students (37.1%) knew how to use fire extinguisher. Statistical test result using chi square test show that there is a relationship between the level of knowledge (0.002) and attitude (0.000) with the level of preparedness in fire disaster preparedness at Islamic Boarding Scholl Pondok Karya at Manado City. Recommended for Islamic Boarding School Management are required to provide education on fire disaster management preparedness to students at least once a year, so that if a fire disaster occurs, the risk can be minimized.